Evaluasi Sistem Keamanan Komputer: Analisis Ancaman, Kriptografi, dan Perlindungan Data Modern - Zul Fadly; Zulkarnaen Lubis; Dendy Rivaldo Alwisyah; Dedy Munandar; Muhammad Riski Afriyansyah (JIKUM: Jurnal Ilmu Komputer, 2026)
Computer security plays a crucial role in protecting the confidentiality, integrity, and availability of digital information in modern computing environments. This study evaluates key computer security components through an analysis of threat models, operating system security mechanisms, cryptographic approaches, and modern data protection techniques. The research reviews user management, firewall configuration, system updates, and layered defense strategies, as well as the characteristics and propagation of contemporary malware such as ransomware, spyware, and network-based attacks. Classical and modern cryptographic methods, hashing functions, digital signatures, and steganography are also examined as essential elements in ensuring secure information processing. Using a descriptive qualitative method supported by literature studies and system observations, the findings indicate that effective computer security requires a multilayered approach supported by consistent system maintenance and increased user awareness to mitigate evolving cyber threats.